(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Distance learning is a method of instruction where lessons are delivered via the Internet and self-learning modules. Students work from home with the guidance of their parents rather than in a classroom. This paper aimed to ascertain the status of distance preschool learning in UCCP Nursery-Kindergarten schools during the pandemic. The study used quantitative research during the first semester of the 2022-2023 school year, with participants including preschool teachers and parents from the United Church of Christ in the Philippines. This study used the descriptive design method, collecting the quantitative data through a survey. According to the findings, the distance preschool learning among UCCP Nursery-Kindergarten Schools exceeded expectations and satisfied both respondents. There is a significant relationship between the status of preschool distance learning and the degree to which the two groups of respondents were satisfied with the educational setup during the pandemic. In addition, there is no significant difference in the satisfaction levels between the two groups of respondents regarding preschool education via distance during the pandemic. Therefore, the researchers recommended a seminar-workshop to enhance the respondents’ use of computer technology in teaching and learning and to improve their knowledge of the curriculum content.